EXAMINING THE EFFECTS OF ENGLISH CAMP ON EFL STUDENTS’ SPEAKING SKILL - Martora, Jasmal; Basri, Megawati; Hasan, Sukarman (JURNAL PASIFIK PENDIDIKAN, 2024)
This research investigates the effectiveness of English camps in facilitating learning without the pressure to ask questions and in delivering instructional material, as well as their potential to enhance students’ speaking skills. The study employed a qualitative research approach, involving 45 students enrolled in the English education program at Universitas Pasifik. The findings indicate that English camps significantly contribute to improving pronunciation skills and create a conducive environment for enhancing overall English proficiency. These camps leverage interactive activities such as games, discussions, presentations, and speaking practices, which collectively foster a supportive atmosphere conducive to language learning and skill development. The implications suggest that English camps hold promise as a supplementary educational tool for enhancing students’ language competencies, particularly in speaking.